Synthesis and Spectral Studies of Zn(II), Cd(II) and Hg(II) Complexes with 1H-Pyrrole-2-carbothioic Acid Dibenzofuran-3-ylamide - SBIRNA, LIANA-SIMONA; REISS, AURORA; PREDA, ANISOARA; CIOLAN, FLORINA (Asian Journal of Chemistry, 2010)
The aim of this paper is to identify 1H-pyrrole-2-carbothioic acid dibenzofuran -3-ylamide (PCADY) is coordinated to Zn(II), Cd(II) and Hg(II), by finding a quantum-mechanical explanation for the spectral data. The study proves that the heteroatoms from the thioamide group are the ones involved in coordination. The result has been verified and confirmed by IR and NMR spectral analyses.